1995
DOI: 10.4037/ajcc1995.4.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Time to hemostasis: a comparison of manual versus mechanical compression of the femoral artery

Abstract: BACKGROUND: Compression of the femoral artery to achieve hemostasis is necessary following angiographic and interventional cardiovascular procedures. OBJECTIVES: To evaluate length of time to hemostasis with manual versus mechanical compression of the femoral artery. METHODS: In a prospective study of 503 patients randomized into one of three groups, manual compression with a pressure dressing or vascular stasis button was used on groups 1 and 3, respectively. Mechanical compression with a pressure dressing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…A mechanical technique, the C‐clamp compression device, was first introduced in 1974 and functions much like a C‐clamp used in carpentry 15–17 . It provides the application of constant pressure while maintaining limb perfusion, and frees up the operator to provide monitoring by only one nurse 17 .…”
Section: Research Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A mechanical technique, the C‐clamp compression device, was first introduced in 1974 and functions much like a C‐clamp used in carpentry 15–17 . It provides the application of constant pressure while maintaining limb perfusion, and frees up the operator to provide monitoring by only one nurse 17 .…”
Section: Research Reviewmentioning
confidence: 99%
“…However, it introduces the risk of malpositioning, which may result in failure to achieve haemostasis 15 . The C‐clamp was compared to manual compression in a number of studies, which generally reported no significant differences in femoral vascular complication rates 15–20 . However, disproportionate sampling designs and small sample sizes might make external validity and reliability questionable.…”
Section: Research Reviewmentioning
confidence: 99%
“…After successful hemostasis by manual compression, 4-6 h of bed rest is required for complete hemostasis prior to ambulation, depending on the size of the sheath or catheter used, or the use of antiplatelets or anticoagulants during the procedure (5). Manual compression has dis- advantages such as being highly time consuming, causing fatigue of the hand and arm, and requiring nursing assistance to monitor the patient (12,13). To overcome the disadvantages of manual compression, other hemostatic methods, such as arterial closure devices (ACDs) and mechanical compression devices, have been developed (5,6,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…18 At the inception of PEI, the standard procedure for closure of the femoral catheterization site was manual pressure and several hours of bedrest. 19,20 The advent of vascular closure devices (VCD) decreased the time to hemostasis and ambulation, but has not decreased the incidence of vascular complications. 4,17 VCD are convenient because they allow for immediate removal of the arterial sheath, but our novel protamine-assisted sheath removal has a similar incidence of complications compared to other studies of access site complications.…”
Section: Discussionmentioning
confidence: 99%
“…During past 3 decades, PEI emerged as an alternative to peripheral bypass surgery for many patients with PAD 18 . At the inception of PEI, the standard procedure for closure of the femoral catheterization site was manual pressure and several hours of bedrest 19,20 . The advent of vascular closure devices (VCD) decreased the time to hemostasis and ambulation, but has not decreased the incidence of vascular complications 4,17 …”
Section: Discussionmentioning
confidence: 99%